2010
DOI: 10.1021/ol1030298
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Oxidative Amination of Benzoxazoles via C−H and C−N Bond Activation: A New Strategy for Using Tertiary Amines as Nitrogen Group Sources

Abstract: An efficient and conceptually new method for oxidative amination of azoles with tertiary amines via copper-catalyzed C-H and C-N bond activation has been developed. This protocol can be performed in the absence of external base and only requires atmospheric oxygen as oxidant. The catalyst system is very simple and efficient, which opens a new way for using tertiary amines as nitrogen group sources for C-N bond formation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(76 citation statements)
references
References 60 publications
1
74
0
1
Order By: Relevance
“…For example, Guo and co-workers demonstrated that an imminium ion, derived from oxidation of a tertiary amine, can undergo C–N bond cleavage via hydrolysis to afford a copper amide species (LnCu–NR 1 R 2 ) which can react further with benzoxazole via a copper mediated C–H insertion to afford the desired aminated product. 1121 Alkyl tertiary amines bearing α–hydrogens reacted efficiently while amines without an α–H failed to react. An increase in yield was observed when a phenyl substituent was installed at the α–position of the amine.…”
Section: Reactions Of Aminesmentioning
confidence: 99%
“…For example, Guo and co-workers demonstrated that an imminium ion, derived from oxidation of a tertiary amine, can undergo C–N bond cleavage via hydrolysis to afford a copper amide species (LnCu–NR 1 R 2 ) which can react further with benzoxazole via a copper mediated C–H insertion to afford the desired aminated product. 1121 Alkyl tertiary amines bearing α–hydrogens reacted efficiently while amines without an α–H failed to react. An increase in yield was observed when a phenyl substituent was installed at the α–position of the amine.…”
Section: Reactions Of Aminesmentioning
confidence: 99%
“…140 This approach could be performed in the absence of an external base with molecular oxygen as the oxidant. This reaction combines the cleavage of the C−N bond and amination of the C−H bond, presenting the utility of tertiary amines as the nitrogen source in the C−H bond activation process.…”
Section: C−n Bond Cleavage Via Imine or Iminiummentioning
confidence: 99%
“…276 The CuBr 2 -catalysed oxidative C−H amination of azoles by atmospheric O 2 in the presence of acetic acid and tertiary amines (acting as base and nitrogen source) forms corresponding amines in good yields thereby providing a powerful method for new C−H amination reactions involving a new strategy for C−N bond activation. 277 Benzylic C−H oxygenation was achieved using 2-benzyl benzonitrile derivatives and p-tolylmagnesium bromide (Grignard reagent) in DMF under O 2 atmosphere with Cu(OAc) 2 catalyst in the presence of K 3 PO 4 . The reaction is proposed to proceed via O 2 oxidation of an iminyl copper intermediate to give a peroxycopper(III) compound, which undergoes intra-molecular 1,5-H-shift with formation of a benzylic radical that proceeds to give a ketoimine via a peroxy copper species.…”
Section: Triplet Oxygen and Autoxidationmentioning
confidence: 99%